Anaesthesia at a glance - Stone, Julian; Fawcett, William 1962- (At a glance series (Oxford, England), 2013)
Anaesthesia at a Glance is a brand new title that provides a concise and visually-orientated summary of a comprehensive lecture course in anaesthesia